Compressive behaviours of novel SCS sandwich composite walls with normal weight concrete - Yan, Jia-Bao; Wang, Zhe; Luo, Yun-Biao; Wang, Tao (Thin-walled structures, 2019)
Novel steel-concrete-steel (SCS) sandwich composite walls with normal weight concrete (NWC) and J-hook connectors have been proposed for shear walls in buildings and protective walls in Arctic offshore platforms. Eight SCS sandwich walls with J-hook connectors and NWC were tested under monotonic compression. Investigated parameters in this testing programme included thickness of steel faceplate, spacing of J-hook connectors, strength of NWC core, and different types of connectors. Based on the reported test results, the influences of these parameters were analysed and discussed. Theoretical models were developed to predict compressive resistance of SCS sandwich walls with different types of connectors. The developed analytical models considered the confinement of steel faceplate on compressive strength of concrete core and proposed new buckling length coefficient for steel faceplate in SCS sandwich wall. The accuracies of the proposed analytical models were checked through validations against 50 test results reported by authors and other researchers. Finally, step-by-step design procedures were proposed to determine compressive resistance of SCS sandwich walls with different types of shear connectors. •Novel SCS sandwich wall was developed for Arctic protective structures.•Steel faceplate thickness improves compressive resistance of SCS sandwich wall.•Composite action influences significantly compressive behaviours of SCS sandwich wall.•Compressive resistance of SCS sandwich wall increases linearly with strength of core.•New theoretical models are developed for compressive resistance of SCS sandwich wall.